THE HUMAN PROBLEMS OF THE SENIOR ACCOUNTANT. - Davis, Kenneth L. (The Accounting Review, 1956)
Abstract This article discusses the role of competent public accountant (CPA) in the business organizations. Technical knowledge is not the only mark of a CPA. Successful pursuit of a career as a CPA requires more than a complete education and experience in applying academic principles, more than accuracy and speed in performing an audit. The CPA who practices on their own account or who acts as in-charge accountant on engagements outside the office cannot long survive without some medium of skill in conducting his relations with the people surrounding them. The degree of this skill frequently determines their course of career. To the average client, the field auditors represent the public accounting firm. The senior accountant must bear the responsibility of representing the firm in worthy fashion. Clients retain public accounting firms partly because of a favorable impression of its staff members. Partners of public accounting firms who perform the personnel function have become increasingly aware of the desirability of the exercise of human relations skill by senior accountants. As modern living becomes more and more complex, social, psychological, and business problems increase proportionately.